(untitled) (Asian Business Research, 2018)
Social norm, an important and coordinating part in economic activities, can greatly reduce the information demand that economic decisions require. The assumption of “Rational Man”, which exists in the western mainstream economics, is based on the simplified model of the instinct of human beings. And this thoroughly ignores the social attribute of human beings. In the literature review, the assumption of “Rational Man” is analyzed as an abstract and deductive way based on the western culture of Christianity. This theory can better explain the economic behaviors of human beings under the specific social circumstance of the protestant ethic. However, its rationality cannot be guaranteed without such cultural background. Besides, under the eastern social circumstance dominated by Confucianism, the assumption of “Rational Man” can also bring prominent ethical conflicts. The assumption of “Information Economic Man” put forward by this thesis gives consideration both to the individual rationality and social features an economic man possesses, and better explains the impact of social norm on economic decisions. By bringing into the capital vector, and drawing on field theory, the model of “information field” is generated. It can provide economic man with a concise math model that affects the process of decision making. The size and direction of capital vector represent respectively the influence of economic factors and moral factors on economic decisions. And thus a wider range of economic behavior of human beings can be analyzed in a rational way.